2010
DOI: 10.1177/1440783310371402
|View full text |Cite
|
Sign up to set email alerts
|

Career confidence and gendered expectations of academic promotion

Abstract: This article discusses expectations of career progression, based on interviews with New Zealand-based university academics. In these interviews, most women said they did not expect to reach the professoriate before retirement while most men said they planned for and anticipated this promotion. The article attempts to explain gendered patterns of career confidence and progression by discussing academic practices and the backgrounds and experiences of academics, drawing on previous research on the ‘gender gap’ a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 19 publications
(27 reference statements)
4
61
0
3
Order By: Relevance
“…Equally, being selected or singled out and explicitly encouraged to apply for promotion or senior positions was an important signifier for those women who lacked confidence and quite often the 'know-how.' This finding resonates with previous research both in the national context and internationally that women's lower confidence levels are influenced by a lack of collegial recognition and esteem [43,63]. Finally, there are indications that gender equality is now on the active agenda in a number of universities; however, while the policy imperative to promote gender equality presented opportunities for women, it was felt that the same policy allowed women to be used by the dominant group as tokens to legitimize the existing system, commodifying what Fitzgerald refers to as 'the cachet of women's diversity' [1] (p. 37).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Equally, being selected or singled out and explicitly encouraged to apply for promotion or senior positions was an important signifier for those women who lacked confidence and quite often the 'know-how.' This finding resonates with previous research both in the national context and internationally that women's lower confidence levels are influenced by a lack of collegial recognition and esteem [43,63]. Finally, there are indications that gender equality is now on the active agenda in a number of universities; however, while the policy imperative to promote gender equality presented opportunities for women, it was felt that the same policy allowed women to be used by the dominant group as tokens to legitimize the existing system, commodifying what Fitzgerald refers to as 'the cachet of women's diversity' [1] (p. 37).…”
Section: Discussionsupporting
confidence: 90%
“…While they recognized that pressure to be visible and present had decreased to some degree over time, they were still of the view that bringing caring responsibilities to work could have a damaging impact on one's profile and ultimately on one's career progression. Again, resonating with research in the international context, participants in this study indicated that the competitive, entrepreneurial nature of the modern university provides significant challenges for those with caring responsibilities, but particularly for mothers [63]. Networks of support, both formal and informal, emerged as important in this study as women increasingly recognized the value of forming intellectual communities which could act in supportive, advisory, and strategic ways.…”
Section: Discussionmentioning
confidence: 55%
“…La extensión de las agencias de evaluación de la calidad (Morley, 2005;Baker, 2010;Mountz et al, 2015) forma parte de este entramado siguiendo la lógica de la contabilización de méritos considerados excelentes. Las instituciones científicas consiguen mejorar sus indicadores gracias al paso de investigadores e investigadoras altamente competitivos que dejan un rastro significativo en las instituciones de acogida en forma de publicaciones, patentes, proyectos financiados y becas conseguidas, pero que han de marcharse cuando finaliza su beca o proyecto.…”
Section: Variaciones Sobre Un Tema La(s) Trayectoria(s) Científica(s)unclassified
“…La fuerte vinculación entre la internacionalización y la excelencia devalúa aquellas carreras menos internacionales y centradas en la creación de conocimientos locales. Los centros de investigación y las universidades están obligados a internacionalizar sus resultados para aumentar su competitividad y su posición en los rankings (Baker, 2010), por lo que, aquellas instituciones más orientadas a referentes locales y con menor orientación internacional parecen abocadas a producir resultados menos "excelentes".…”
Section: Variaciones Sobre Un Tema La(s) Trayectoria(s) Científica(s)unclassified
“…In the 1960s, New Zealand science, both in DSIR and in the universities, was dominated by male academics, with few women reaching the highest positions [Brooks, 1997;Baker, 2010;Gregory, 2014]. The international feminist movement of the 1970s and 80s, plus the election of the Helen Clark Labour Government in 1989, led to increased numbers of women in leadership in New Zealand [Curtin, 2008].…”
Section: New Zealand Women In Sciencementioning
confidence: 99%